Prevalence of hepatitis B and C viruses among hemodialysis patients in Southern West Bank, Palestine - Badareen, Khaled Z. (International Journal of Research in Medical Sciences, 2016)
Background: In addition to severe renal impotence and decline of immune status, the high prevalence of hepatitis B and C virus’s infection represents one of the most critical clinical problems that are implicated in the progression of severe complication among hemodialysis patients. This study was performed to estimate the prevalence of hepatitis B and C viruses among hemodialysis patients and to recognize the pattern of chronic disease that will access to the renal failure. Methods: In this retrospective cohort study, data were collected from 252 hemodialysis patients for the presence of HBsAg, anti-HCV antibody, and the primary chronic disease that causes renal failure, in March 2013 from three governmental hospitals in southern West Bank in Palestine. Results: From 252 HD patients, 59% were male and 41% were female. 78% of them ranged between 15 and 65 years. 6.7% of all patients were HBsAg positive and 8.7% were anti-HCV antibodies are positive. Diabetes mellitus (33.7%), hypertension (23.7%), and chronic nephritis (6.0%), represent the most known primary chronic diseases that causes end stage renal disease. Conclusions: The role of the chronic diseases in accession to the renal failure, and the high prevalence of hepatitis B and C virus infection among hemodialysis patients compared to the normal healthy population indicate a causative relation between hemodialysis and hepatitis virus transmission.